The effect of Physical Educational Class in Identifying Physical and Verbal Aggressive Behaviour for the Fourth intermediate Class in the Governorate of Djelfa. - Brahimi, Tarek (Journal of Human Sciences, 2022)
The Object of the study .identify to both physical and verbal aggressive behaviour during the physical educational class, for the Fourth intermediate class students, for this purpose, we used the method  Descriptive On a sample composed of 330 students Chosen as sample random, and for data collection, we used a tool questionnaire After collecting the results and having treated them statistically, we conclude 1) Moderate aggressive behaviour both verbally and physically as the percentage of the physical aggression is 2.14 and verbal aggression is 2.13 out of 4 points. 2) There is a correlation between the verbal and physical aggression with a coefficient of 0.74. The study recommends developing and enhancing the physical educational curriculum so as to absorb the students’ potentials and vent them out properly through participations in sports and safe activities, which would allow students to attain emotional.